Phytochemical Profile Extracts and Fractions of Pisitan Monyet (Dysoxylum caulostachyum Miq.) - Bonor, Toga; Among, Sayyid; Febriyanti, Raden Maya; Maisyarah, Intan Timur; Barliana, Melisa Intan (Indonesian Journal of Biological Pharmacy, 2024)
Dysoxylum is a genus from the Meliaceae family which has 905 species. One species of this genus is Dysoxylum caulostachyum Miq. This species is a plant that has long been consumed as daily food for primates. This plant is starting to be widely researched for its potential for treatment. There are several previous studies showing that D. caulostachyum has antiproliferative, antiplasmodial and anticancer bioactivity. The aim of this paper is to determine the phytochemical profile of D. caulostachyum leaves in the ethanol extract, n-hexane fraction and ethyl acetate fraction of D. caulostachyum leaves. The research was carried out through extraction stages using the maceration method, fractionation using Liquid-Liquid Extraction (ECC), examination of extracts and fractions using Thin Layer Chromatography (TLC), phytochemical screening, and measurement of total phenolic and total flavonoid levels. Based on phytochemical screening, D. caulostachyum leaf extract contains flavonoids, saponins, polyphenols, monoterpenes/sesquiterpenes, quinones, and triterpenes/steroids. The n-Hexane fraction of D. caulostachyum leaves contains quinone compounds, the ethyl acetate fraction of D. caulostachyum leaves contains flavonoids, quinones and polyphenol compounds, while the water fraction of D. caulostachyum contains polyphenol and quinone compounds. From the extract and leaf fractions of D. caulostachyum, data was obtained that the extract contained the highest levels of total phenolics and flavonoids, namely 92.361 ± 1.7245 mg GAE/g and 92.361 ± 1.7245, respectively.